Characterization of a self‐aligned RTD using a SiNx sidewall process for high‐speed applications. Issue 12 (22nd September 2017) - Lee, Kiwon; Lee, Hoyeon; Lee, Jongwon
Abstract: In this article, an InP‐based self‐aligned resonant‐tunneling‐diode (RTD) using a SiNX sidewall process has been fabricated and characterized for high‐speed microwave applications. A plasma‐enhanced dry‐etch technique has been used to form a vertical emitter mesa. The measured peak currents are almost constant at a peak voltage due to negligible thermionic emission in a wide temperature range up to 125°C. The extracted series resistance of the fabricated self‐aligned RTD is 14.5 Ω, which is reduced by 27% compared with that of the nonself‐aligned RTD by reducing the spacing between emitter mesa and collector metal. To the best of authors' knowledge, this is the first attempt to characterize a self‐aligned RTD using the dry‐etched mesa and the SiNX sidewall structure.